2010
DOI: 10.1097/paf.0b013e3181c160d9
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Intoxication

Abstract: The nervous system has increased susceptibility for methanol intoxication. The aim of this study is to investigate various central nervous system lesions of methanol intoxication in 17 cases autopsied in the mortuary department of the Council of Forensic Medicine in Istanbul, Turkey. The reasons of methanol intoxication in the cases was likely the unwitting ingestion of methanol while drinking illegal alcohol. Survival times ranged from several hours to days. In 8 cases (47%), cerebral edema and in 9 cases (53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 4 publications
5
11
0
Order By: Relevance
“…Pathology in the pons was reported in a case where it was demonstrated that foci of T2 hyperintensity in the bilateral pontine tegmentum was one of the imaging findings in severe methanol intoxication [ 10 ]. Further, in a case series of 17 patients who died of methanol intoxication, pontine hemorrhage was documented in 2 cases on autopsy [ 11 ]. The susceptibility of the pons to methanol is worth investigating, as its vulnerability with the optic nerve may not be a coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology in the pons was reported in a case where it was demonstrated that foci of T2 hyperintensity in the bilateral pontine tegmentum was one of the imaging findings in severe methanol intoxication [ 10 ]. Further, in a case series of 17 patients who died of methanol intoxication, pontine hemorrhage was documented in 2 cases on autopsy [ 11 ]. The susceptibility of the pons to methanol is worth investigating, as its vulnerability with the optic nerve may not be a coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…They had similar plasma methanol concentrations at approximately the same time after ingestion, but one patient developed brain death, and the other recovered without sequelae. 12 The pathway of methanol metabolism 2 and some of the mechanisms of injury to the optic nerve 3 , 13 and brain 14 , 15 are now relatively well understood. Methanol itself is relatively non-toxic and can be excreted unaltered through the lungs and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…A number of neuropathologic 14 and neuroimaging 24 , 25 studies have described the typical central nervous system (CNS) pathology of methanol poisoning. The most common CNS injury is bilateral hemorrhagic or non-hemorrhagic necrosis of the putamen, occurring in roughly half of all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Methanol is commonly found in solvents, deicers, glass cleaners, as well as homemade alcohols (“moonshine”). It is metabolized to formic acid which can cause neurologic injury, optic nerve toxicity, and retinal injury resulting in vision impairment [151–153]. Ethylene glycol is found in antifreeze, brake fluids, and coolants and has a sweet taste which makes it attractive to animals and small children.…”
Section: Discussionmentioning
confidence: 99%